Career development management in Sabah Sports Board / Maniah Runggi @ Azwina - Runggi @ Azwina, Maniah (2012)
Leibowitz, Farren & Kaye, 1986; Lips-Wiersma & Hall, 2007 pointed out that Career Development is a process where employees strategically explore, plan, and create their future at work by designing a personal learning plan to achieve their potential and fullfil the organization's learning, seeking opportunities, taking risks, and finding ways to contribute to the organization in a productive and motivated fashion. To achieve a balance between an individual’s career needs and the organization’s workforce requirements, it involves an organized, formalized and planned effort. Organizations can encourage employees to manage their own careers while employees need to follow through with the responsibility of managing their own career development. The organization can also promote more employees from within their company because they have developed and easily identified their internal leaders. Career developments programs provide opportunities for employees to thrive in their current job and at the same time supplying the means to make either a horizontal or vertical career move possible.